OP008 α4β7 Integrin-dependent gut homing of non-classical monocytes is essential for intestinal wound healing mediated by M2 macrophages. (16th January 2018) - Schleier, L; Wiendl, M; Binder, M -T; Atreya, R; Watson, A; Neufert, C; Atreya, I; Neurath, M F; Zundler, S
Abstract: Background: The anti-α4β7 integrin antibody Vedolizumab is successfully used for the treatment of IBD. Mechanistically, it is well established that it inhibits α4β7 integrin-dependent gut homing of pathogenic T lymphocytes to the inflamed gut. However, the impact of anti-α4β7 treatment on monocyte gut homing, which differentiate to macrophages regulating intestinal inflammation and tissue remodelling, has not been investigated so far. Methods: Expression of gut homing integrins on peripheral blood monocyte and intestinal macrophage subsets from IBD patients and controls was analysed by flow cytometry and immunohistochemistry, respectively. Dynamic adhesion assays were used to investigate monocyte adhesion to mucosal addressin vascular cell adhesion molecule (MAdCAM)-1 with or without vedolizumab treatment. Monocyte subset homing to the inflamed gut was studied in mice in vivo. Moreover, mouse models were used to assess intestinal wound healing with and without anti-α4β7 antibodies and the proportion of macrophage subsets was quantified by immunohistochemistry. Flow cytometric distribution of monocyte subsets was measured in patients treated with vedolizumab. Results: While the expression of α4β7 was low on overall monocytes, human CD16 + intermediate and non-classical monocytes and murine CX3CR1 + non-classical monocytes expressed high levels of α4β7 (Figure 1A and B) and other homing markers typically expressed by lymphocytes. Homing marker expression in classical monocytes and CD14 + intestinal macrophages was similar while the pattern observed in non-classical monocytes rather resembled that of CD163 + macrophages, thus supporting earlier reports indicating a preferential differentiation of non-classical monocytes to M2 macrophages. Anti-α4β7 treatment inhibited dynamic adhesion of human monocytes in vitro and gut homing of murine monocytes in vivo (Figure 1C). Intestinal wound healing in mice treated with anti-α4β7 antibodies (Figure 1D) and in β7−/− mice was impaired going along with reduced numbers of M2 macrophages. In IBD patients treated with vedolizumab, the proportion of CD16 + monocytes increased over the course of treatment. Conclusions: In addition to blocking lymphocyte homing to the gut, anti-α4β7 treatment also impedes non-classical monocyte homing. This leads to reduced presence of M2 macrophages surrounding mucosal wounds and impaired intestinal wound healing potentially providing an explanation for the recent clinical observation of increased postoperative complications in vedolizumab-treated patients. Disclosure: Support provided by Takeda.